Attitudes to hormone management in dairy cow reproduction. Issue 6 (November 2013) - Higgins, Helen; Murray, Richard; Black, David; Christie, Mike; Crawley, Madeleine
<x xml:space="preserve">Abstract</x> Oestrus detection in Holstein cows is difficult. Hormones to induce oestrus or for fixed‐time artificial insemination are now commonly prescribed to facilitate, or remove the need for, detection of oestrus. The acceptability of pharmaceutical intervention to overcome short fallings in management is discussed, including from the wider perspective of global food security. Public perception and the veterinary profession's engagement with the public over potentially controversial issues are raised.